2020
DOI: 10.29252/jhehp.6.1.6
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Escherichia coli O157:H7 Inoculated in Hamburger Using a Chitosan/Cellulose Nanofiber Film Containing the Nanoemulsion of Trachyspermum ammi and Bunium persicum Essential Oils

Abstract: The Inhibition of E. coli O157:H7 in Hamburger Using a Chitosan Film Soltaninezhad B, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It has been observed that the basal diet give satisfactory results [ 823 ]. The Trachyspermum ammi EO (NTEO), and Bunium persicum EO (NBPEO) have been used to prepare chitosan based nanoemulsions and chitosan based nanoemulsions have been applied to hamburgers to improve its microbial quality [ 875 ]. 1–2% of Bunium persicum EO along with tween 80 (emulsifier), and glycerol (plasticizer) have been used to make chitosan films and the films have been applied on chicken fillet to retard its chemical spoilage and to improve its microbial quality [ 425 ]…”
Section: Food Industry Application Of Selected Spicesmentioning
confidence: 99%
“…It has been observed that the basal diet give satisfactory results [ 823 ]. The Trachyspermum ammi EO (NTEO), and Bunium persicum EO (NBPEO) have been used to prepare chitosan based nanoemulsions and chitosan based nanoemulsions have been applied to hamburgers to improve its microbial quality [ 875 ]. 1–2% of Bunium persicum EO along with tween 80 (emulsifier), and glycerol (plasticizer) have been used to make chitosan films and the films have been applied on chicken fillet to retard its chemical spoilage and to improve its microbial quality [ 425 ]…”
Section: Food Industry Application Of Selected Spicesmentioning
confidence: 99%
“…Pathogenic strains of Escherichia coli and Staphylococcus aureus can compromise the microbial safety of food products due to improper preparation and distribution practices (Haghi et al, 2019;Lee & Yoon, 2021;Newell et al, 2010;Soltaninezhad et al, 2020). Another concern that threatens consumer safety is the oxidation process in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the efforts of regulatory bodies, scientists, and industrialists, foodborne pathogens continue to cause significant damage to national economies and the social welfare of populations. Pathogenic strains of Escherichia coli and Staphylococcus aureus can compromise the microbial safety of food products due to improper preparation and distribution practices (Haghi et al., 2019 ; Lee & Yoon, 2021 ; Newell et al., 2010 ; Soltaninezhad et al., 2020 ). Another concern that threatens consumer safety is the oxidation process in foods.…”
Section: Introductionmentioning
confidence: 99%